Raised plasma arginine vasopressin concentrations during cluster headache attacks. Issue 4 (October 1995) - Franceschini, R; Leandri, M; Cataldi, A; Bruno, E; Corsini, G; Rolandi, E; Barreca, T
Abstract : To obtain data about peripheral concentrations of arginine vasopressin in head pain syndromes, the plasma arginine vasopressin secretory pattern in 12 adult male patients with cluster headache was evaluated. Blood samples for plasma arginine vasopressin and osmolality determinations were collected before, and at 15, 30, 45, 60, 90, and 120 minutes during a cluster attack. Blood pressure was also monitored. The same sampling was repeated during an asymptomatic period. During cluster attacks, the mean values of plasma arginine vasopressin before an attack (2.3 (0.1) ng/l) significantly increased, reaching their peak at 45 minutes (4.8 (0.5) ng/l; P < 0.01 v baseline). No significant variations were found in mean arterial pressure and plasma osmolality. These data suggested involvement of neurotransmitter mechanisms regulating arginine vasopressin secretion and a possible role of arginine vasopressin in vasomotor phenomena accompanying cluster attacks.